2014
DOI: 10.1039/c4ra09749a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic signatures and structural motifs in isolated and hydrated caffeine: a computational study

Abstract: The conformational landscapes of neutral caffeine and its hydrated complex have been investigated by MP2 and DFT methods. The ground state geometry optimization yields six lowest energy structures for bare caffeine and five lowest energy conformers of the caff 1 -(H 2 O) 1 complex at the MP2/6-311++G(d,p) level of theory for the first time. We investigated the low-lying excited states of bare caffeine by means of coupled cluster singles and approximate doubles (CC2) and TDDFT methods and a satisfactory interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
(185 reference statements)
1
13
0
Order By: Relevance
“…In such conformers, phenol interacts with caffeine through π⋅⋅⋅π interactions and a hydrogen bond with C=O of caffeine. This assignment would be in agreement with previous studies on caffeine–water, in which water was also found to interact preferentially with the carbonyl groups of caffeine . However, no consensus was found between them for the relative stability of the local minima.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In such conformers, phenol interacts with caffeine through π⋅⋅⋅π interactions and a hydrogen bond with C=O of caffeine. This assignment would be in agreement with previous studies on caffeine–water, in which water was also found to interact preferentially with the carbonyl groups of caffeine . However, no consensus was found between them for the relative stability of the local minima.…”
Section: Resultssupporting
confidence: 91%
“…In such conformers, phenol interacts with caffeine through p···p interactions and ah ydrogen bond with C=Oo fc affeine.T hisa ssignment would be in agreement with previous studies on caffeine-water,i nw hich water was also found to interact preferentially with the carbonyl groups of caffeine. [44,45,65] However,n oc onsensus was found between them for the relative stabilityo ft he local minima. This seems to indicatet hat the methods used are abletoa ccurately model stronger interactions, but they balance other weaker interactions in different ways.…”
Section: Resultsmentioning
confidence: 99%
“…The VEE to the same L b ( 1 pp*) state for Sero 1 -(H 2 O) 1 involving conformer Gph(out)/anti (C) is red shied by 314 cm À1 and for the strongly H-bonded Sero 1 -(H 2 O) 2 complex involving the same conformer C, it (VEE to the L b ( 1 pp*) state) was signicantly red shied by 1287 cm À1 in comparison to monomer. 52 The corresponding red shi (in L b ( 1 pp*) state) for Sero 1 -(H 2 O) 1,2 involving C conformation shows that S 0 -S 1 electronic transition increases the strength of the hydrogen bonds to water. 22 Thus the blue shi in L b ( 1 pp*) state of Sero 1 -(H 2 O) 1 (see Fig.…”
Section: Vertical Excitation Energies Of Serotonin-water Complexesmentioning
confidence: 98%
“…A blue shi for a p-p* transition is also attributed to the reduction in the p-electron conjugation length of the molecule due to the hydrogen bond formation. 52 The corresponding red shi (in L b ( 1 pp*) state) for Sero 1 -(H 2 O) 1,2 involving C conformation shows that S 0 -S 1 electronic transition increases the strength of the hydrogen bonds to water. Interestingly the VEE to the optically bright state 1 L a ( 1 pp*) of Sero 1 -(H 2 O) 1 (see Fig.…”
Section: Vertical Excitation Energies Of Serotonin-water Complexesmentioning
confidence: 98%
“…In the experimental IR spectra 1 the carbonyl stretching modes consists of two major bands; the higher wavenumber band and the lower wavenumber band. Similar to caffeine 42,43 the two C]O groups of theophylline couple into an in phase C]O stretching vibration and an out of phase stretching vibrations. The out of phase (C]O) 2 stretching mode is observed at a lower frequency while the in-phase mode is observed at higher frequency.…”
Section: Optimized Geometries Of Theophylline Monomer and Its Hydrate...mentioning
confidence: 99%